Migration of phthalates and 2,6-diisopropylnaphthalene from cellulose food packaging - Coltro,Leda (2021)
Abstract Recycling systems are unable to remove efficiently all potential contaminants acquired along the recycling chain. Therefore, contaminants may potentially exist in recycled food packaging. The safety of recycled cellulose food-contact materials depends on the toxicity and the ability of post-consumer contaminants to be absorbed by recycled fibers released by the packaging and ultimately absorbed by the food. Furthermore, the migration of different contaminants is related to their levels of contamination, structures and chemical affinity with cellulose fibers. In this study, twenty samples of cellulose packages available in the Brazilian market were evaluated regarding migration of phthalates (dibutyl phthalate – DBP, diisobutyl phthalate – DIBP and bis(2-ethylhexyl) phthalate – DEHP) and 2,6-diisopropylnaphthalene – DIPN into fatty food simulant using GC-FID. Fifty percent of the cellulose packaging samples showed no migration of DIPN or of any phthalates evaluated, whereas 20% showed migration of DIBP, 15% migration of DBP and 40% migration of DEHP.